Vascular wilt caused by Fusarium oxysporum in agave (Agave tequilana Weber var. azul) - Ávila-Miranda, Martín E.; López-Zazueta, José G.; Arias-Castro, Carlos; Rodríguez-Mendiola, Martha A.; Guzmán-de Peña, Doralinda A.; Vera-Núñez, José A.; Peña-Cabriales, Juan J. (Journal of the Professional Association for Cactus Development, 2010)
Agave tequilana Weber var. azul is a crop used to produce ‘Tequila’ in Mexico. The agave’s wilting (marchitez in spanish) is an economically important disease associated to Fusarium oxysporum. The symptoms reported in the diseased plants include extensive stem and root rot that are uncharacteristic of vascular wilt associated to F. oxysproum in other crops. Ten agave commercial fields presenting high agave’s wilting incidence in the Mexicos’s Jalisco and Nayarit states were evaluated. A severity scale was used in the field to evaluate agave’s wilting and, in general, a positive correlation was observed between the degree of xylem vascular damage or root rot with the wilt severity level in the field plants. Twenty–one isolates of F. oxysporum obtained from stem tissue of agave plants were analyzed to determine their genetic diversity using Box–PCR DNA markers. A group of ten strains with identical fingerprints was identified including isolates from distant fields. Five strains from three genetic groups were used to test their pathogenicity in agave plants propagated in vitro under greenhouse conditions. Wilt symptoms were observed in agave plants 200 days after inoculation of the F. oxysporum strains. The incidence of blocked or partially degraded xylem vessels was higher in plants inoculated with any of the F. oxysporum strains as compared to the control plants. The root rots symptom was not present in inoculated plants. Interestingly, several Fusarium solani isolates were obtained from rooting roots or stem of field diseased plants, indicating that at least two Fusarium species are responsible for agave’s wilting disease.